An Alkyne Diboration/6π‐Electrocyclization Strategy for the Synthesis of Pyridine Boronic Acid Derivatives. Issue 19 (5th April 2016) - Mora‐Radó, Helena; Bialy, Laurent; Czechtizky, Werngard; Méndez, María; Harrity, Joseph P. A.
Abstract: A new and efficient synthesis of pyridine‐based heteroaromatic boronic acid derivatives is reported through a novel diboration/6π‐electrocyclization strategy. This method delivers a range of functionalized heterocycles from readily available starting materials. Abstract : Get in the ring ! β‐Alkynyl α, β‐unsaturated oximes undergo a alkyne diboration/6π‐electrocyclization sequence to deliver a range of pyridine boronic acid derivatives. The scope of this method to deliver useful heterocyclic products is described.